Comparative study of Automated Auditory Brainstem Response (AABR) and Brainstem Evoked Response Audiometry (BERA) for Hearing Loss Detection in High Risk Infants delivered in Dhulikhel Hospital - Karmacharya, Sameer; Shrestha, Bikash Lal; K.C., Abha Kiran; Pradhan, Aakash; Shrestha, Ayushi; Ghimire, Saroj Babu (Janaki Medical College Journal of Medical Science, 2023)
Background & Objective: Brainstem evoked response audiometry (BERA) is most specific and sensitive test for brain stem dysfunction. It is most important objective method for evaluating peripheral auditory system in neonates, infants, sedated and comatose patients and other person who doesn’t understand the language. Objective of the study was to evaluate correlation BERA with other audiological tests in different types of hearing loss. Material and Methods: This was a hospital based retrospective observational analytic study that used a cross-sectional approach. The sampling used was consecutive sampling until the minimum size fulfilled from 1st September 2021 to 30th September 2022. All high-risk infants aged 0–3 months who suffer from asphyxia, sepsis, LBW, premature, and hyperbilirubinemia, the baby was stable and transportable, the patient’s parents were willing to participate were taken. Results: Out of 46 high risk infants of 0 - 3 months, male:female ratio of 1.7:1 with mean age of 31 days, the most common high risk factor was low birth weight and hyperbilirubinemia i.e 23(50%). 64% of infants were pass in AABR 2nd test in comparison to 71% pass in BERA test. Conclusion: There was no difference between AABR and BERA results for HL detection in high-risk infants at NICU.